Low voltage high speed 8T SRAM cell for ultra-low power applications - S. S. Trinadh Kumar, A; V. V. Satyanarayana, B (International Journal of Engineering and Technology, 2018)
The usage of portable devices increasing rapidly in the modern life has led us to focus our attention to increase the performance of the SRAM circuits, especially for low power applications. Basically in six-Transistor (6T) SRAM cell either read or write operation can be performed at a time whereas, in 7T SRAM cell using single ended write operation and single ended read operation both write and read operations will be accomplished simultaneously at a time respectively. When it comes to operate in sub threshold region, single ended read operation will be degraded severely and single ended write operation will be severely degraded in terms of write-ability at lower voltages. To encounter these complications, an eight transistor SRAM cell is proposed. It performs single ended read operation and single ended write operation together even at sub threshold region down to 0.1V with improved read-ability using read assist and improved dynamic write-ability which helps in reducing the consumption of power by attaining a lower data retention voltage point. To reduce the total power consumption in the circuits, two extra access transistors are used in 8T SRAM cell which also helps in reducing the overall delay.Â Â